Damping torque analysis of power systems with DFIGs for wind power generation. Issue 1 (5th September 2016) - Du, Wenjuan; Bi, Jingtian; Lv, Chen; Littler, Tim
Abstract : A grid‐connected double fed induction generator(DFIG) for wind power generation can affect power system small‐signal angular stability in two ways: by changing the system load flow condition and dynamically interacting with synchronous generators (SGs). This study presents the application of conventional method of damping torque analysis (DTA) to examine the effect of DFIG's dynamic interactions with SGs on the small‐signal angular stability. It shows that the effect is due to the dynamic variation of power exchange between the DFIG and power system and can be estimated approximately by the DTA. Consequently, if the DFIG is modelled as a constant power source when the effect of zero dynamic interactions is assumed, the impact of change of load flow brought about by the DFIG can be determined. Thus the total effect of DFIG can be estimated from the result of DTA added on that of constant power source model. Applications of the DTA method proposed in this study are discussed. An example of multi‐machine power systems with grid‐connected DFIGs is presented to demonstrate and validate the DTA method proposed and conclusions obtained in this study.